Land suitability evaluation for cereal crops: a multicriteria approach using GIS at Parbatipur VDC, Chitwan, Nepal - Neupane, B.; Shriwastav, C. P.; Shah, S. C.; Sah, K. (Journal of the Institute of Agriculture and Animal Science, 2018)
A research was conducted to evaluate the suitability of soils of different land unit for cereal crops productions at Parbatipur VDC, Chitwan, Nepal with the integrated use of Geographical Information system (GIS) and Multi-criteria evaluation (MCE).Existing geodatabase information from National Land Use Project (NLUP) was used as data for this research. The database was used to derive crop suitability using vector based index model in GIS along with multicriteria analysis. The research revealed that for rice cultivation, 1.06 %(10.70ha) was highly suitable,51.54 %(515.89ha) was moderately suitable, 3.39% (33.987 ha) was marginally suitable but 28.28 %( 283.11 ha) was not suitable whereas for wheat cultivation, 7.6%(76.73ha) was highly suitable, 44.91% (449.53 ha) was moderately suitable and 4.6% (46.26ha) was marginally suitable, but 27.15% (27.14ha) was not suitable. Similarly, for maize cultivation, 12.07% (120.83ha) was highly suitable, 40.19% (402.25ha) was moderately suitable and 0.53% (5.37ha) was marginally suitable, but 31.54% (315.72ha) was not suitable for maize production. Hence, the area not suitable for rice, wheat and maize must be allocated for alternative uses to achieve optimum productions and further there must be new research for alternative land uses in VDC, where these crops were not suitable for optimum productions. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, Page: 55-64